2023
DOI: 10.3390/pharmaceutics15010256
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Interface: Improved Pulmonary Surfactant-Assisted Drug Delivery through Surface-Associated Structures

Abstract: Pulmonary surfactant (PS) has been proposed as an efficient drug delivery vehicle for inhaled therapies. Its ability to adsorb and spread interfacially and transport different drugs associated with it has been studied mainly by different surface balance designs, typically interconnecting various compartments by interfacial paper bridges, mimicking in vitro the respiratory air–liquid interface. It has been demonstrated that only a monomolecular surface layer of PS/drug is able to cross this bridge. However, sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Carriers include traditional liposomes, NPs, and micro hydrogels. Additionally, pulmonary surfactants have been suggested as powerful medication delivery systems for inhalation therapy [ 170 ].…”
Section: Delivery System For Pulmonary Drug Deliverymentioning
confidence: 99%
“…Carriers include traditional liposomes, NPs, and micro hydrogels. Additionally, pulmonary surfactants have been suggested as powerful medication delivery systems for inhalation therapy [ 170 ].…”
Section: Delivery System For Pulmonary Drug Deliverymentioning
confidence: 99%
“…A study revealed that Au NPs utilizing Hygrophila spinosa leaf extract showed anticancer, antibacterial, and antifungal activity against several tested pathogens [151]. NPs are used widely in drug delivery for asthma patients [152].…”
Section: A Nigermentioning
confidence: 99%